Turning defence into offence? Intrusion of cladoceran brood chambers by a green alga leads to reproductive failure - Dania Albini (Royal Society Open Science, 2020)
We observed a novel anti-grazer strategy in the green alga Chlorella vulgaris, where the cells entered the brood chambers of two grazers, Daphnia magna and Simocephalus sp, densely colonized the eggs, and significantly reduced the grazers' reproductive success.